1997
DOI: 10.1038/sj.onc.1201227
|View full text |Cite
|
Sign up to set email alerts
|

Induction of senescence in human malignant glioma cells by p16INK4A

Abstract: p16INK4A is a G1-speci®c cell cycle inhibitor which maps to human chromosome 9p21, a region frequently mutated or deleted in cancer cell lines and primary tumors. In glioblastomas the frequency of homozygous deletions is 40 ± 70% making it one of the most common mutations in this tumor type. We have analysed the signi®cance of the loss of this gene in gliomas by introducing the cDNA for p16INK4A into the human glioma cell line U-1242 MG which has a deleted CDKN2 locus. We used the tetracycline repressable vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 29 publications
(37 reference statements)
10
64
1
Order By: Relevance
“…However, a reduced expression of CD28 has previously been observed during T-lymphocyte senescence (Perillo et al, 1993), an e ect that was observed also in our system. Furthermore, we observed an induction of SA-b-gal activity in the aged Tlymphocytes, which has been shown to be a biomarker for senescence in other cellular systems (Dimri et al, 1995;Uhrbom et al, 1997). This demonstrates that SAb-gal activity can be used also for analysing senescence in T-lymphocytes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, a reduced expression of CD28 has previously been observed during T-lymphocyte senescence (Perillo et al, 1993), an e ect that was observed also in our system. Furthermore, we observed an induction of SA-b-gal activity in the aged Tlymphocytes, which has been shown to be a biomarker for senescence in other cellular systems (Dimri et al, 1995;Uhrbom et al, 1997). This demonstrates that SAb-gal activity can be used also for analysing senescence in T-lymphocytes.…”
Section: Discussionsupporting
confidence: 62%
“…At the initiation of the culture the majority of the cells expressed CD28 (Figure 2a), whereas the non-proliferating cells at the end of the culture had virtually abolished their expression of this marker (Figure 2b). b-gal (b-gal) staining at pH 6.0, referred to as Senescence-Associated b-galactosidase (SA-b-gal), has been shown to be a reliable marker for senescence in other cellular systems by (Dimri et al, 1995;Uhrbom et al, 1997). We found that 1 ± 2% of un-stimulated T-cells have detectable SA-b-gal activity.…”
Section: Characterization Of Senescencementioning
confidence: 85%
“…Moreover, upregulation of p16 ink4a a member of the ink4 family, has been observed during the late stages of senescence, where proliferation ceases terminally (Alcorta et al, 1996). Consistent with a role in regulating senescence, p16 ink4a expression was lost in mammary epithelial cells that escaped from the M0 proliferation block (Foster et al, 1998) and ectopic expression of p16 ink4a induced termination of proliferation and a senescence-like state in human glioma cells (Uhrbom et al, 1997).…”
Section: Introductionmentioning
confidence: 79%
“…In mammary epithelial cells inactivation of p16 ink4a by CpG island methylation was shown to be associated with escape from the M0 proliferation block (Foster et al, 1998). Moreover, engineered expression of p16 ink4a in a human glioma cell line with a p16 ink4a deletion led to the onset of senescence, as determined by induction of senescencespeci®c b-galactosidase activity and was accompanied by changes in cellular morphology (Uhrbom et al, 1997). We observed very similar e ects, including a dramatic increase in cell size in SCC15 cells both in response to re-expression of endogenous p16 ink4a and when p16 ink4a expression was enforced by a retrovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Both cell lines were isolated from human glioblastomas and various characteristics have been described (Bigner et al, 1981;Bongcam-Rudloff et al, 1991;Uhrbom et al, 1997;Hussaini et al, 1999). U-1242-Z cells are U-1242 cells that stably express PKC-Z (Hussaini et al, 2000).…”
Section: Cell Culturesmentioning
confidence: 99%